Multichannel Fetal Ecg Extraction and Enhancement Using Triggered Adaptive Filtering Augmented with Weighted Transitions - Badee, Versal; Dansereau, Richard M.; Chan, Adrian D.C. (CMBES Proceedings, 2007)
In this paper, we extend the adaptive noise cancellation (ANC) and adaptive system identification (ASI) methods for noninvasive fetal electrocardiogram (FECG) extraction and enhancement, respectively, by including an adaptation trigger augmented with weighted transitions. These techniques are applied to remove unwanted interferences from a multichannel noninvasive abdominal measurement, with the dominating interference being the maternal ECG (MECG). Evaluation of this method was performed on data which used an externally applied electrical stimulus pulse (SP) to simulate the FECG. A current pulse was applied to a subject’s lower back and acquired from multiple channels on the abdomen. Our results indicate that the use of triggering with linearly weighted transitions outperforms triggering with on/off transitions and no triggering, with an improvement in the estimated SNR of 12.5 % and 36.2 %, respectively .